2021
DOI: 10.1093/braincomms/fcab053
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4-dependent lactate dehydrogenase activation as a protective response to amyloid beta toxicity

Abstract: Accumulation of amyloid beta peptides is thought to initiate the pathogenesis of Alzheimer’s disease. However, the precise mechanisms mediating their neurotoxicity are unclear. Our microarray analyses show that, in Drosophila models of amyloid beta 42 toxicity, genes involved in the unfolded protein response and metabolic processes are upregulated in brain. Comparison with the brain transcriptome of early-stage Alzheimer’s patients revealed a common transcriptional signature, but with generally opposing direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Lipid synthesis is another critical component of myelin biogenesis and maintenance that may be positively regulated by ATF4 [52][53][54] . Moreover, ATF4 is a positive regulator of the lactate generating anerobic glycolysis, which is highly active in OLs to support axonal oxidative metabolism 55,56 , a mechanism which involves increased expression of the key lactate producing enzyme lactate dehydrogenase (LDH) 56 . Noteworthy, the Ldha transcript that encodes one of the two principal LDH isoforms in mammals shows a biphasic upregulation in SCI OL translatome that correlates with biphasic induction of ATF4/CHOP at dpi 2 and dpi 42 (4.86 and 3.84 fold naïve control, respectively, q<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid synthesis is another critical component of myelin biogenesis and maintenance that may be positively regulated by ATF4 [52][53][54] . Moreover, ATF4 is a positive regulator of the lactate generating anerobic glycolysis, which is highly active in OLs to support axonal oxidative metabolism 55,56 , a mechanism which involves increased expression of the key lactate producing enzyme lactate dehydrogenase (LDH) 56 . Noteworthy, the Ldha transcript that encodes one of the two principal LDH isoforms in mammals shows a biphasic upregulation in SCI OL translatome that correlates with biphasic induction of ATF4/CHOP at dpi 2 and dpi 42 (4.86 and 3.84 fold naïve control, respectively, q<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we found that neuronal dLdh upregulation caused an increase in the number of brain vacuoles [51], indicative of neurodegeneration occurring in the fly brain with age [96]. Other studies in flies have recently shown that the toxic effect of amyloid beta, a peptide strongly implicated in neurodegeneration in Alzheimer’s disease, causes dLdh upregulation in part due to an Activating transcription factor 4 (ATF-4) dependent endoplasmic reticulum stress signalling unfolded protein response [52]. In accordance with our findings on neuronal dLdh impact on fly survival, the authors of this study also found that both upregulation and downregulation of neuronal dLdh caused an exacerbation of amyloid beta toxicity [52].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in flies have recently shown that the toxic effect of amyloid beta, a peptide strongly implicated in neurodegeneration in Alzheimer's disease, causes dLdh upregulation in part due to an Activating transcription factor 4 (ATF-4) dependent endoplasmic reticulum stress signalling unfolded protein response [52]. In accordance with our findings on neuronal dLdh impact on fly survival, the authors of this study also found that both upregulation and downregulation of neuronal dLdh caused an exacerbation of amyloid beta toxicity [52]. Furthermore, a recent finding demonstrated that ubiquitous disruption of the Ldhb gene within mice resulted in increased mitochondrial dysfunction, oxidative stress, apoptosis, and cognitive impairment [97].…”
Section: Discussion Dldh Expression Needs To Be Precisely Regulated T...mentioning
confidence: 99%
See 1 more Smart Citation
“…ATF4 is a signaling molecule downstream of the Endoplasmic reticulum-resident kinase (PERK) pathway in the ER stress signaling pathway (Moulin et al, 2020). ATF4 plays an important role in ontogeny, cellular stress response, amino acid secretion, apoptosis and tumorigenesis (Niccoli et al, 2021;Chen et al, 2021a). As shown in Fig.…”
Section: Imoxin Alleviates the Expression Of Er Stress Induced By Sepsis In Renal Tissuementioning
confidence: 99%